Changes in Oxidized Low-Density Lipoprotein Rather Than in Paraoxonase1 are Associated with Changes in the Leptin/Leptin Receptor Ratio in Obese Children During Weight-Loss Therapy - Gajewska, Joanna; Chełchowska, Magdalena; Ambroszkiewicz, Jadwiga; Riahi, Agnieszka; Weker, Halina; Szamotulska, Katarzyna (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background Oxidative stress and impaired production of adipokines in childhood obesity contribute to the development of obesity-related disorders. We assessed whether weight loss after lifestyle intervention alters biomarkers of oxidant/antioxidant status, and whether these alterations are associated with changes in anthropometric parameters and adipokines in obese children.Materials and Methods We determined oxidized low-density lipoprotein (ox-LDL), anti ox-LDL, paraoxonase1 (PON1), leptin, soluble leptin receptor (sOB-R), total adiponectin, high molecular weight adiponectin concentrations and body composition (by dual-energy X-ray absorptiometry) in 60 prepubertal obese children (Body Mass Index, BMI Z-score>2) before and after a 3-month intervention. The control group consisted of 44 non-obese children (BMI Z-score<−1+1>).Results Ox-LDL, ox-LDL/LDL, and anti ox-LDL concentrations as well as leptin to sOb-R ratio were reduced (p<0.001; p=0.018; p<0.001; p<0.001, respectively) in obese children with weight loss (BMI Z-score change≤−0.5) after a 3-month therapy. These parameters were stable in the obese group without weight loss (BMI Z-score change>−0.5). Changes in ox-LDL and PON1 levels in all obese children correlated positively with changes in the leptin to sOB-R ratio (r=0.400, p=0.002; r=0.304, p=0.028, respectively). After adjustment for changes in BMI Z-score in the multivariate regression model, the association between the changes in ox-LDL levels and changes in the leptin/sOb-R ratio remained statistically significant (β=0.184, p=0.014).Conclusions We found out that a 3-month lifestyle intervention associated with weight loss improves the oxidant/antioxidant balance and promotes anti-atherogenic changes in prepubertal obese children in a way dependent on the alterations in the leptin to sOB-R ratio.
Keywords: ox-LDL; PON1; anti ox-LDL; adipokines; prepubertal period